2022
DOI: 10.3390/life12060835
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Airspace Alterations after Using the Mandibular Advancement Device in the Treatment of Obstructive Sleep Apnea Syndrome

Abstract: Background: Mandibular Advancement Devices (MADs), inserted in non-surgical treatments for obstructive sleep apnea and hypopnea syndrome (OSAHS), are used intra-orally during the sleep period, with the aim of promoting mandibular protrusion. The aim of the study is to analyze the changes in the upper airway after the use of an MAD in the treatment of OSAHS. Methods: 60 patients diagnosed with OSAHS, as established by the Sleep Medicine Service, underwent treatment with the Silensor SL device at the Stomatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…In the present study, more changes were observed in the volume of the NA, followed by the laryngopharynx than in the oropharynx, presenting a notable increase in air permeability at points A, MCI and very prominent at Pg, unlike point B. which reflected minor changes. This does not agree with the other studies analyzed such as that of Ferraz et al 2022 and Bariana et al 2022 [12,21], in which many of these changes were noted especially in the upper pharynx, and were of small to moderate magnitude, meaning that changes in the nasopharynx could have little clinical relevance. In contrast, greater effects were observed in the lower pharynx, indicating that any clinically relevant benefits in airway dimensions or breathing could be attributed to this compartment, consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In the present study, more changes were observed in the volume of the NA, followed by the laryngopharynx than in the oropharynx, presenting a notable increase in air permeability at points A, MCI and very prominent at Pg, unlike point B. which reflected minor changes. This does not agree with the other studies analyzed such as that of Ferraz et al 2022 and Bariana et al 2022 [12,21], in which many of these changes were noted especially in the upper pharynx, and were of small to moderate magnitude, meaning that changes in the nasopharynx could have little clinical relevance. In contrast, greater effects were observed in the lower pharynx, indicating that any clinically relevant benefits in airway dimensions or breathing could be attributed to this compartment, consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…According to Do Vale et al 2019, an explanation for the improvement of the airway at point Pg and less at point B, is due to the rotation of the occlusal plane counter clockwise, described as a movement that optimizes the gain of space in the airways. Respiratory [12,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation